Regional dimension of growth and employment - Ramaswamy, K.V. (2007)
Regional inequality has emerged as a key issue in recent discussions of development policy. States within India differ greatly in terms of economic growth and employment potential. This paper examines some aspects of this regional employment growth in India during 1983 to 2004-05. The results confirm widening interstate disparities in income in the first quinquennium on the 21st century, a continuation of the trend of the 1990s. Urban employment occurs strongly in initially urbanised states. All states are found to be diversifying, but at a slower pace in low income states. A geographic concentration of skilled labour is observed in financial and business services. - Reproduced.
Keywords: Employment; Economic growth